AGN and Star Formation in HerMES-IRS sources. Issue Volume 9:Issue S304(2013) (25th July 2014) - Feltre, Anna; Hatziminaoglou, Evanthia; Hernán-Caballero, Antonio; Fritz, Jacopo; Franceschini, Alberto; ,
Abstract: One of the remaining open issues in the context of the analysis of Active Galactic Nuclei (AGN) is the evidence that nuclear gravitational accretion is often accompanied by a concurrent starburst activity. We developed a spectral energy distribution (SED) fitting technique to derive simultaneously the physical properties of active galaxies and coexisting starbursts making the best use of Spitzer and Herschel IR observations. We apply the SED fitting procedure to a large sample of extragalactic sources representing the HerMES ( Herschel /Multi-tiered Extragalactic Survey) population with IRS spectra with a plethora of multi-wavelength data in order to study the impact of a possible presence of an AGN on the host galaxy's properties. We analyze the star formation rate (SFR) in conncetion to the presence of an AGN and compared the properties of the hot (AGN) and cold (starburst) dust component. Our findings are consistent with no evidence for the presence of an AGN affecting the star formation processes of the host galaxies.